2018
DOI: 10.5694/mja17.01109
|View full text |Cite
|
Sign up to set email alerts
|

Differences in management and outcomes for men and women with ST‐elevation myocardial infarction

Abstract: The known Sex differences in the management and outcomes of patients with acute coronary syndromes have been reported, but many reported analyses were not adjusted for confounding covariates.The new Despite broader awareness of STEMI protocols, revascularisation rates for women with STEMI are lower than for men. In hospital, rates of major adverse cardiovascular events and mortality were similar, but at 6 months were significantly higher for women. Women were less frequently referred for cardiac rehabilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
115
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 22 publications
4
115
2
3
Order By: Relevance
“…We could not identify the time from the onset of symptoms or first medical contact to either treatment or to arrival at the first hospital. Earlier studies have found longer time to reperfusion among women, so it is possible that late presentation is a reason for lower revascularization rates among women in our study. Also, because women have atypical symptoms, there may be a selection bias whereby providers do not recognize these symptoms, and women in the study are more ill than the population of women with STEMI.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…We could not identify the time from the onset of symptoms or first medical contact to either treatment or to arrival at the first hospital. Earlier studies have found longer time to reperfusion among women, so it is possible that late presentation is a reason for lower revascularization rates among women in our study. Also, because women have atypical symptoms, there may be a selection bias whereby providers do not recognize these symptoms, and women in the study are more ill than the population of women with STEMI.…”
Section: Discussionmentioning
confidence: 63%
“…Other studies have shown that women with STEMI are less likely to undergo revascularization or reperfusion than their male counterparts . For example, in a study of 632,930 patients using the Nationwide Inpatient sample databases from 2004 to 2011, Khera et al reported that younger women (age <60 years old) presenting with STEMI were less likely to undergo PCI (AOR = 0.74 [0.73, 0.75]) and less likely to undergo CABG surgery (AOR = 0.61 [0.60, 0.62]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disparity in health status and the delivery of evidence‐based treatment for cardiovascular disease based on sex and socio‐economic status (SES) is extremely concerning . Gender inequality in the treatment and outcomes post‐acute coronary syndrome has been extensively reported in the medical literature as has a marked female predominance in the incidence of heart failure with preserved ejection fraction . The same cannot be said for heart failure with reduced ejection fraction (HFrEF).…”
Section: Introductionmentioning
confidence: 99%